Automatic classified myocardial infarction detection using machine learning and forewarning system with location of the patient using GSM module - Shrestha, Soptorsi Paul; Amin, Md. Hasnatul; Faisal, MD. Amir; Alam, Syed Md. Jawadul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.